The Evaluation of the Successful Integration Implementation of Academic Information System I-Gracias and CeLOE Learning Management System at Telkom University Using DeLone and McLean Model - Ramadhan, Miftah; Trias Hanggara, Buce; Hayuhardhika Nugraha Putra, Widhy (Journal of Information Technology and Computer Science, 2024)
Telkom University has implemented data integration on the I-Gracias Academic Information System with the CeLOE Learning Management System (LMS) to make it easier for students to carry out the course registration process. However, each semester, the course registration process still has several problems. This research aims to assess the success rate of implementing the integration between the I-Gracias and CeLOE LMS systems based on student perceptions and analyze the correlation between variables from the DeLone and McLean models. The research used the descriptive analysis and Rank Spearman correlation analysis involving 100 respondents. This research collected data by purposive sampling technique and distributing questionnaires using Google Forms. The results of the descriptive analysis obtained an overall proportion of 81.75%, which is in the High category. However, there are still two variables with values below the mean, service quality with the lowest indicator of responsiveness and user satisfaction with the lowest indicator of effectiveness, expectations, and satisfaction with system performance. The results of the correlation analysis show that the correlation between system quality and user satisfaction in the Very Strong category, system quality and use in the Moderate category, service quality and user satisfaction in the Moderate category, service quality and use in the Low category, and other correlation variables in the Strong category. The success of implementing the integrated system between I-Gracias and CeLOE LMS can be increased by implementing 8 recommendations for improvement on indicators that are still below the mean.